Correlation between muscle tissue and type 2 diabetes - Noga, Rafal; Marcinkowska, Jagoda; Miśkiewicz, Marek; Ptak, Jakub; Herc, Adrian; Sawczuk, Marcelina; Koczkodon, Karolina; Teska, Victoria; Perłowski, Jakub; Krompiewski, Mariusz (Quality in Sport, 2024)
Diabetes is one of the most common diseases in the world. There are several types of it with different etiologies. The most common type of diabetes is type 2. Every year, DM2 contributes to the deaths of millions of people worldwide. Its complications pose a huge health as well as economic problem. Nowadays, pharmaceutical companies are outdoing themselves in synthesizing new drugs, using newer and newer mechanisms of action. This meets with the approval of patients – It is easier to take a pill instead of changing your lifestyle. However, it is worth considering and rethinking the pathophysiology of type 2 diabetes. How to effectively reduce the risk of pre-diabetes or developing DM2? In this research study, we will try to give an insight into how important our body’s muscle tissue is in the context of diabetes and why it is important to take care of its proper amount and condition. It is hoped that paying attention to this aspect in relation to diabetes will allow for a less invasive and more effective treatment of carbohydrate disorders and contribute to benefiting from the other health effects of developing proper skeletal muscle tissue in the human body.